Application Of Pcq (Per Connection Queue) In Limiting Bandwidth With The Simple Queue Method At Smkn 1 Seluma - Yosef Anggara; Sari , Herlina Latipa; Suryana, Eko (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The internet network at SMK Negeri 1 Seluma often experiences disruptions when used simultaneously by many users, causing a decline in signal quality and connection difficulties. This study aims to implement bandwidth management so that 30 Mbps internet access can be distributed evenly to three local networks, namely the Administration Room (15 Mbps), the Teacher's Room (10 Mbps), and the Laboratory (5 Mbps). The method used is the PPDIOO approach (Plan, Prepare, Design, Implement, Operate, Optimize) with Per Connection Queue (PCQ) configuration using Simple Queue on the Mikrotik router. Testing was conducted via speedtest before and after PCQ implementation in each room. The results show that bandwidth, which was previously not distributed proportionally, can now be distributed more fairly to each user. For example, in the TU room after PCQ implementation, each of the three clients received relatively equal bandwidth. The implementation of PCQ with Simple Queue proved effective in limiting and dividing bandwidth among users in a balanced manner and improving the overall stability of the school network.